Behavioral barrier of bubble and light dispersion associated with the protection of ichthyofauna in the hydroelectric sector - Melo Neto, Miguel Vieira de; Silva, Tania Machado da; Fernandes, Tarek Rodrigo; Sargentini Junior, Ézio; Zara, Luiz Fabricio (Technical and Scientific Journal Green Cities, 2025)
The present article aims to investigate the effectiveness of a behavioral barrier composed of a bubble curtain and permanent light to protect fish fauna during operational maneuvers in hydroelectric plants, aiming to mitigate environmental impacts. For this purpose, instrumental aquariums were used with five species of juvenile fish (Cichlasoma amazonarum, Dianema urostriatum, Pimelodus blochii, Brycon spp. and Colossoma macropomum). The experiments were filmed in three stages: before, during and after barrier activation. The behavior of the fish was analyzed by counting in specific sectors every 15 seconds. The gap filled by research on behavioral barriers in tropical aquatic environments, using native species and contributing to mitigating the impacts of hydroelectric technologies on fish fauna. Activating the barrier significantly reduced the presence of fish in sectors close to the barrier, with an average efficiency of 82% in deterring individuals. Species such as Matrinxã and Acará Amazônico demonstrated greater efficiency in avoiding the barrier. The study indicates that the bubble curtain in conjunction with permanent light has high potential for protecting ichthyofauna, aiming to prevent the entry and confinement of ichthyofauna during operational maneuvers in the hydroelectric sector.